1-stage bilateral total hip arthroplasty operation in 22 patients with use of short and standard stem length on either side: gait analysis 1 and 2 years after bilateral THA. Issue 4 (July 2018) - Zügner, Roland; Tranberg, Roy; Puretic, Goran; Kärrholm, Johan
Background: According to previous gait analyses, insertion of a total hip arthroplasty (THA) will improve the range of hip flexion-extension but not to normal. Use of short stems could have a potential to improve the motion by preservation of more bone and muscular attachments. We evaluated whether a short femoral stem resulted in improved hip motion compared to a conventional stem in patients who underwent 1-stage bilateral THA. The most painful hip was randomised to either design and the 2 nd hip was operated with the design not used on the 1 st side. Methods: Gait analysis was performed with an optical tracking system in 22 patients. The follow-up was performed 1 and 2 years after the operation. The mean age was 59 (SD 7.7) years and body mass index was 27.7 (SD 4.3). 66 subjects without hip pathology served as controls. Results: Minimal differences were observed, between or within the 2 different stem designs during gait at the 2 follow-up occasions. Comparison between each of the 2 stem designs and controls at 2 years revealed reduced stride length (p = 0.009), cadence, hip extension (p<0.001) and hip extension-flexion range (p = 0.021) for both designs. Furthermore, the range of hip adduction-abduction (p = 0.046) and hip abduction moment for both designs in the frontal plane was also reduced bilaterally (p<0.001). Conclusions: We found no difference in gait parameters between the short and the conventional stem after 1-stage bilateral THA. Although both hip joints were operated at the same time motions and moments did not normalise after bilateral 1-stage operations.